Community Readiness in Implementing E-Government in Online Services at the Pratama Tax Service Office in Palopo City - Widyastuti, Try; Madani, Muhlis; Hakim, Lukman; Mappasere, Fatmawati A. (Jurnal Manajemen Pelayanan Publik, 2024)
Electronic-based government, or e-Government, has gained popularity along with the development and advancement of information and communication technology The public's growing demands are in line with technical advancements intended to make life easier and better for people. Yet the community's preparedness for its execution hasn't been the best. The Pratama Tax Service Office in Palopo makes this clear. Researchers employed primary and secondary data sources to collect data. Interviews were used to gather primary data, and material previously processed by other academics provided secondary data. The primary goal of this study was to gather data on the implementation of e-government, which aims to change the way services are provided to the public. E-Government is a system of government administration that makes use of information and communication technology, especially when it comes to public services. As a result, several factors, including technological, economic, globalized, national, and local ones, affect how e-government develops.